Investigation of Surface Properties and Free Volumes of Chitosan-Based Buccal Mucoadhesive Drug Delivery Films Containing Ascorbic Acid - Katalin Kristó; Szilvia Módra; Viktória Hornok; Károly Süvegh; Krisztina Ludasi; Zoltán Aigner; András Kelemen; Tamás Sovány; Klára Pintye-Hódi; Géza Regdon (MDPI AG, 2022)
Nowadays, the buccal administration of mucoadhesive films is very promising. Our aim was to prepare ascorbic acid-containing chitosan films to study the properties and structures important for applicability and optimize the composition. During the formulation of mucoadhesive films, chitosan as the polymer basis of the film was used. Ascorbic acid, which provided the acidic pH, was used in different concentrations (2-5%). The films were formulated by the solvent casting method. The properties of films important for applicability were investigated, such as physical parameters, mucoadhesive force, surface free energy, and breaking strength. The fine structure of the films was analyzed by atomic force microscopy, and the free volume was analyzed by PALS, which can be important for drug release kinetics and the location of the drug in the film. The applicability of the optimized composition was also tested with two different types of active ingredients. The structure of the films was also analyzed by XRPD and FTIR. Ascorbic acid can be used well in chitosan films, where it can function as a permeation enhancer when reacting to chitosan, it is biodegradable, and can be applied in 2% of our studies.